Blowup for a Non-Newtonian Polytropic Filtration System Coupled via Nonlinear Boundary Flux. (1st April 2008) - Li, Zhongping; Mu, Chunlai; Li, Yuhuan
Abstract : We study the global existence and the global nonexistence of a non-Newtonian polytropic filtration system coupled via nonlinear boundary flux. We first establish a weak comparison principle, then discuss the large time behavior of solutions by using modified upper and lower solution methods and constructing various upper and lower solutions. Necessary and sufficient conditions on the global existence of all positive (weak) solutions are obtained.